Preparing for Cardiopulmonary Bypass: A Simulation Scenario for Anesthesia Providers - Brett Myers; Clark Obr (Association of American Medical Colleges, 2017)
Introduction This simulation on cardiopulmonary bypass (CPB) introduces learners to the relevant critical actions and concepts involved in going onto and off of CPB. It is intended that junior residents experience this simulation immediately prior to beginning their cardiac anesthesia rotation. Thus, this simulation serves to segue to the trainee's initial clinical experience with CPB. Methods The case is fully presented for facilitators in the simulation case file, which includes a brief narrative description of the case, learning objectives to be covered by the simulation, and a summary of critical actions to be performed by the learner during the educational activity. It is optimal to run this simulation using a high-fidelity human patient simulator with anesthesia machine and relevant monitors. Results The simulation was carried out by eight CA-1 or CA-2 residents during the 2016 academic year. Cardiac anesthesia faculties observed a significantly improved learning curve for trainees who had experienced this simulation prior to their first clinical case. Discussion Overall, this simulation has been found to be a very effective learning tool at the University of Iowa. To that end, this simulation has been incorporated into the cardiac anesthesia curriculum, and all junior residents experience this simulation prior to beginning their rotation.